11x-(2-x)=52

Simple and best practice solution for 11x-(2-x)=52 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x-(2-x)=52 equation:


Simplifying
11x + -1(2 + -1x) = 52
11x + (2 * -1 + -1x * -1) = 52
11x + (-2 + 1x) = 52

Reorder the terms:
-2 + 11x + 1x = 52

Combine like terms: 11x + 1x = 12x
-2 + 12x = 52

Solving
-2 + 12x = 52

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 12x = 52 + 2

Combine like terms: -2 + 2 = 0
0 + 12x = 52 + 2
12x = 52 + 2

Combine like terms: 52 + 2 = 54
12x = 54

Divide each side by '12'.
x = 4.5

Simplifying
x = 4.5

See similar equations:

| f(5h-6)=x^2-5x-3 | | 3-(-12)=4a-a | | 49x^2-25y^2=16 | | 240+2y=460 | | 80-0.25Q=15+Q | | -1x=-80 | | 6x^2+17x-14=25 | | 8q+3b=12 | | 23x=136 | | D=-50m+500 | | 18m+4n=138 | | 5(4x+6)=-190 | | 2x-5=11+x | | 4*y=60 | | 10x+28=6x-28 | | 12y^3+1y^2-6y=0 | | -x-10=-6x+45 | | 0=-20x^2+320x-780 | | (A+7)(a-1)=20 | | 0.5x+0.2y=4.05 | | .5(x+5)=36 | | .5x=36+5 | | 5=4+i | | .5x+5=36 | | 12.00+0.15x=10.00+0.25x | | .5(x-5)=36 | | x=4x-24 | | .5a(x-5)=36 | | f(-3)=3x^2-x | | .5a+5=36 | | 3sinx-4sin^3x=1-2sin^2x | | .25x+5=36 |

Equations solver categories